Private Solutions for Infrastructure in Lesotho. - Bank, World (World Bank, 2005)
Infrastructure in Lesotho is relatively undeveloped with poor coverage and low-quality services common to many African countries that have low per capita incomes and government fiscal limitations that constrain infrastructure investment. This report finds that private participation in infrastructure could offer Lesotho three key advantages: (1) augmenting budget resources in cases where the private sector undertakes to finance projects or services that would not otherwise be funded, (2) improving the quality and efficiency of service delivery, and (3) accelerating investments in infrastructure.